2018
DOI: 10.1111/odi.12973
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonsurgical periodontal treatment on gingival crevicular fluid stress hormone levels: A prospective study

Abstract: Within the limits of the study, decreased GCF COR and unchanged GCF DHEA levels were determined in nonsurgically treated patients regardless of the extent and severity of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The NCT04315532 trial evaluated the impact of periodontal treatment on estrogen and dehydroepiandrosterone (DHEA) levels, whereas the NCT01422122 study assessed the role of vitamin D supplementation. It was shown that DHEA levels correlated with PD severity [ 168 ]. Non-surgical treatment did not influence DHEA levels [ 169 ].…”
Section: Clinicaltrialsgov Analysismentioning
confidence: 99%
“…The NCT04315532 trial evaluated the impact of periodontal treatment on estrogen and dehydroepiandrosterone (DHEA) levels, whereas the NCT01422122 study assessed the role of vitamin D supplementation. It was shown that DHEA levels correlated with PD severity [ 168 ]. Non-surgical treatment did not influence DHEA levels [ 169 ].…”
Section: Clinicaltrialsgov Analysismentioning
confidence: 99%
“…Odds ratio for depression among periodontitis vs controls 1.28 (95% CI 0.56–2.95). fair Case-control studies (Human): Total studies with positive associations between IPD and MD: 6; negative associations: 0; not shown or unclear: 1 Prospective cohort studies (Human) Cakmak et al. (2019) , Turkey 55:15 healthy controls; 40 subjects with periodontitis Dental outpatients, 40.4 (26–63) yrs., 40% women Patients with chronic localized and generalized periodontitis vs healthy controls Localized or generalized chronic periodontitis (based on PI, GI, BOP, PPD, CAL).…”
Section: Resultsmentioning
confidence: 99%
“…IgG against Bacteroides forsythus specifically related to periodontitis patients with depression. Prospective cohort studies (Human) Cakmak et al. (2019) Cortisol, DHEA GCF/ELISA Higher cortisol (pg/ml) levels in localized (338.2 ​± ​309) and generalized (388.0 ​± ​368) chronic periodontitis compared to patient controls (81.4 ​± ​27) p ​< ​0.001.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aimed to evaluate the impact of depression and anxiety assessed with STAI and BDI questionnaires on periodontal treatment outcomes. The French versions of STAI and BDI were selected due to their strong validation, reliability, internal consistency and extensive use in order to evaluate the association between psychological status and chronic diseases [38][39][40][41]. In a previous analysis where depression level was measured using the depression score of the DASS-42 self-administered questionnaire, an association between depression and worsened SRP outcomes was observed, especially regarding the evolution of BOP and reduction in deep sites with PPD > 5 mm and >7 mm [20].…”
Section: Discussionmentioning
confidence: 99%